NF-κB Signaling Contributes to Mechanical Ventilation-Induced Diaphragm Weakness - Smuder, Ashley J. (2012)
BACKGROUND: Although mechanical ventilation (MV) is a life-saving measure for patients in respiratory failure, prolonged MV results in diaphragmatic weakness due to fiber atrophy and contractile dysfunction. Therefore, identifying the signaling pathways responsible for MV-induced diaphragmatic weakness is important. In this context, it is established that oxidative stress is required for MV-induced diaphragmatic weakness to occur. Numerous redox-sensitive signaling pathways exist in muscle including the transcription factor nuclear factor-κB (NF-κB). Although it has been suggested that NF-κB contributes to proteolytic signaling in inactivity-induced atrophy in locomotor muscles, the role that NF-κB plays in MV-induced diaphragmatic weakness is unknown. OBJECTIVE: We tested the hypothesis that NF-κB activation plays a key signaling role in MV-induced diaphragmatic weakness and that oxidative stress is required for NF-κB activation. DESIGN: Cause and effect was determined by independently treating mechanically ventilated animals with either a specific NF-κB inhibitor (SN50) or a clinically relevant antioxidant (curcumin). MEASUREMENTS AND MAIN RESULTS: Inhibition of NF-κB activity partially attenuated both MV-induced diaphragmatic atrophy and contractile dysfunction. Further, treatment with the antioxidant curcumin prevented MV-induced activation of NF-κB in the diaphragm and rescued the diaphragm from both MV-induced atrophy and contractile dysfunction. CONCLUSIONS: Collectively, these findings support the hypothesis that NF-κB activation plays a significant signaling role in MV-induced diaphragmatic weakness and that oxidative stress is an upstream activator of NF-κB. Finally, our results suggest that prevention of MV-induced oxidative stress in the diaphragm could be a useful clinical strategy to prevent or delay MV-induced diaphragmatic weakness.